Image Characterization of Cancer of the Colon - Thaimi Conde Cueto; Martha Yudey Rodríguez Pino; Pedro Juan Barrios Fuentes; Bárbara Aleida García Hernández; Julio Suz Piña; Nery M. Díaz Yanes (Medisur)
Background: Cancer of the colon is the second cause of death due to cancer worldwide, alter lung cancer in males and breast cancer in females. It is not possible to confirm the patient’s diagnosis without the result of image tests such as barium enema, ultrasound cytology or biopsy of the lesion. Objective: To characterize cancer of the colon through images. Methods: Descriptive study which included all the patients discharged from “Dr. Gustavo Aldereguía Lima” General Hospital with a confirming diagnosis of cancer of the colon. The variables under study were: sex, age, past and family history of the disease, its way of presentation, location, image findings and histological diagnosis. Shi square was used for a 95 % exactitude where p<= 0,05. Results: Cancer of the colon was more frequently detected in the age group of 50 to 59 years of age in both sexes meanwhile in the age group 70 to 79 years of age the disease affected males. It was mainly associated to idiopathic ulcerative colitis and to family history of cancer of the colon and cholecystectomy. Suggestive symptoms were predominant in the findings. The most frequent location was in the left part of the colon. There was correlation between the results of the ultrasound and barium enema the X-rays. Conclusion: Ultrasound was of great usefulness, but barium enema is the test of choice in our environment for the diagnosis of cancer of the colon.